Synthesis and characterisation of Cu–TiO2 nanocomposite produced by thermochemical process. (14th March 2016) - Sorkhe, Y. A.; Aghajani, H.; Taghisadeh Tabrizi, A.
Abstract : Cu–TiO2 nanocomposite powders were synthesised by thermochemical process. The composite powders (containing 0, 2.5, 5 and 7 wt-% of TiO2 ), prepared by spray drying of the (aqueous) solution of copper nitrate and titanium nitrate followed by heat treatment at 900°C for 1 h and reduction in hydrogen atmosphere at 500°C for 1 h. The composite powders were prepared by cold pressing and then sintering at 900°C for 1 h. Studies on their microstructures have been carried out through X-ray diffraction, scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Mechanical properties and electrical conductivity of sintered specimens were measured, and the effect of TiO2 content on these properties was investigated. The results showed that the nanosized TiO2 particles (with a diameter of about 10–30 nm) was successfully formed and dispersed within the copper matrix. By introducing TiO2 particles up to 2.5 weight percept, the electrical conductivity wastage is very high.